Development and Validation of an Arduino‑Based Control Algorithm for an Electronic Differential in Quad In‑Wheel Hub Motor Electric Vehicles - Taha, Zeedan; Aydın, Kadir (New Energy Exploitation and Application, 2025)
This paper presents the development and validation of a control algorithm for an Arduino-based EDS EV. The main goal of this system is to improve the speed and torque distribution between the wheels while maneuvering, focusing especially on cornering. The suggested algorithm regulates the throttle signal supplied to each wheel based on the steering angle, using a mathematical model derived from the Ackermann-Jeantand geometry. Initial simulations were run in MATLAB/Simulink to validate the theoretical approach before its real-world implementation. Arduino Uno board was used to adjust the throttle pedal voltage signal for each wheel at low, medium, and high acceleration performance. The response of the voltage supplied to the inner and outer wheels while changing the steering angle had been analyzed. The voltage on the inner wheels decreased when increasing steering angle, while it increased on the outer wheels. Compared to the simulation results, the experimental results indicate minor differences, which can be referred to the effect of noise and the limited accuracy of the hardware used. The results indicate that the Arduino-based EDS system can achieve precise torque distribution of EVs. This study forms a basis for the implementation of the system on a full-scale prototype for performance evaluation under actual driving conditions.